Crimes cometidos por idosos : considerações criminológicas - Monteiro, Simone Ribeiro (2013)
This dissertation was based on interdisciplinary review and analysis of offenses committed by the elderly, through a literature research and case studies from the estate court São Paulo and Rio Grande do Sul. Firstly itself by first current population aging and its prospects for the future highlighting need for further development in respect of offenses in question before increase in the number of elderly and their likely impact on offenses they committed. The statistics back progressive increase in the number of elderly prisoners. We searched what offenses were commonly committed by elderley describing and analyzing each case in order to understand the reasons that took them to commit such crimes and that the penalty applied and the same is different because of the age of agent. Strengthening this line study on the subject were presented after some important considerations about aging the conditions for the application nonimputability these criminal cases followed by approaches to the treatment of the elderly in criminal law. Only after these measures these are the offenses committed by elderly and then complete the research by exposing the possible policies to be applied in such cases. The dissertation is connected to the search "Criminology and Social Control" area of concentration "System and Criminal Violence" Program of Graduate Studies in Criminal Sciences, Pontifícia Universidade Católica do Rio Grande do Sul under the guidance of Doctor Alfredo Neto Cataldo. The interdisciplinary approach is essential because it was necessary to study gerontology marked by this aspect and understandings medical psychological and sociological inherent theme